Mapas Conceituais Colaborativos: uma proposta de ensino para desenvolvimento dos Eixos Estruturantes da Alfabetização Científica em uma turma de Ensino Fundamental 2 - Leme, Idelzuite Azevedo Alcântara (Universidade Federal de São Carlos, 2025)
In a context of falling vaccination coverage rates and distrust regarding the safety and efficacy of vaccines, this study proposes the development and application of a Potentially Significant Teaching Unit (LUPU) that addresses: how vaccines work; their role in maintaining individual and collective health; and the process of vaccine production and approval. Using the Theory of Meaningful Learning (TAS) as a theoretical framework and the Conceptual Map (CM) as a teaching tool, this research project aimed to investigate the potential of using collaborative CM as a subsidy for the implementation of Scientific Literacy (SC) in a seventh-grade class of a municipal school in Sorocaba. The research, classified as exploratory qualitative, used as data collection instruments the CMs produced by the students, the teacher's Logbook notes, and the audio transcripts of the CM presentations and three interviews conducted after the application of the UEPS. As an indication of the development of SC, the occurrence of the three Structuring Axes of Scientific Literacy (EEAC) proposed by Sasseron (2008) was considered: the first axis is the understanding of fundamental scientific terms and concepts; the second axis is the understanding of the nature of science and the ethical and political factors related to its practice; and the third axis is the understanding of the relationships between science, technology, society, and the environment. For the analysis of the MC, the four reference parameters of a good conceptual map described by Aguiar; Correia (2013) were observed. In the interactions between the students, we sought to observe the occurrence of the four stages of the collaborative knowledge construction process: externalization; elicitation; consensus oriented towards integration or conflict; and integration process. We also point out that the first three processes were described by Fischer et al (2002) and the last by Aguiar; Ballego; Correia (2022). As a result, it is worth highlighting that it was possible to observe the presence of the first and third EEAC; regarding the second axis, our hypothesis is that it would be necessary to have a greater number of classes to carry out discussions and reflections that the axis demands. The analysis of the MCs prepared by the groups throughout the UEPS indicated advances in their structure with network-type MC and the presence of cross-links in two groups, and only in one of the groups did the data indicate that new training was necessary tbetter master the mapping technique. Regarding the interaction between group members, the data indicated the occurrence of four stages of the collaborative knowledge construction process.
Collaborative Conceptual Maps: a teaching proposal for the development of the Structuring Axes of Scientific Literacy in a 2nd grade Elementary School class
Mapas Conceptuales Colaborativos: una propuesta didáctica para el desarrollo de los Ejes Estructurantes de la Alfabetización Científica en una clase de 2º grado de Educación Primaria
Keywords: Eixo Estruturante da Alfabetização Científica; Mapa Conceitual; Aprendizagem Colaborativa; Structuring Axis of Scientific Literacy; Conceptual Map; Collaborative Learning; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM